2016
DOI: 10.1139/cjc-2015-0308
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of metal cations from the wet ionic liquid [EMIM][TFSI]

Abstract: Keyword: electrodeposition, wet ionic liquid, possible application to mining wastes https://mc06.manuscriptcentral.com/cjc-pubs We investigated the deposition of silver, copper, and lead from the ionic liquid 1-11 ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide [EMIM][TFSI] under 12potentiostatic conditions in the presence of water. This was part of a larger project 13 involving the extraction of metal ions from mining waste into an ionic liquid, followed by 14 electrodeposition so that the ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…[ 41 ] The electrodeposition of Pb from first‐generation chloridoaluminate ILs has been extensively studied, and in these systems, lead chloride (PbCl 2 ) was used, which is a synthetic compound. [ 42,43 ] Using second‐generation ILs, Pb has been successfully electrodeposited from wet [EMIm][NTf 2 ] ([EMIm] + = 1‐ethyl‐3‐methylimidazolium), [ 44,45 ] [BMPyrr][NTf 2 ] ([BMPyrr] + = 1‐butyl‐1‐methylpyrrolidinium), [ 46 ] and the distillable IL dimethylammonium‐dimethylcarbamat (DIMCARB), [ 47 ] respectively. However, lead dioxide (PbO 2 ) and lead sulfate (PbSO 4 ), which are main components of the lead‐acid battery, are insoluble in the mentioned ILs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] The electrodeposition of Pb from first‐generation chloridoaluminate ILs has been extensively studied, and in these systems, lead chloride (PbCl 2 ) was used, which is a synthetic compound. [ 42,43 ] Using second‐generation ILs, Pb has been successfully electrodeposited from wet [EMIm][NTf 2 ] ([EMIm] + = 1‐ethyl‐3‐methylimidazolium), [ 44,45 ] [BMPyrr][NTf 2 ] ([BMPyrr] + = 1‐butyl‐1‐methylpyrrolidinium), [ 46 ] and the distillable IL dimethylammonium‐dimethylcarbamat (DIMCARB), [ 47 ] respectively. However, lead dioxide (PbO 2 ) and lead sulfate (PbSO 4 ), which are main components of the lead‐acid battery, are insoluble in the mentioned ILs.…”
Section: Introductionmentioning
confidence: 99%
“…20 Numerous ILs have been used for the electrodeposition of silver. 11,[21][22][23][24][25][26][27][28][29][30][31][32][33] However, various silver salts such as AgNO₃, AgCl, AgBF₄ and etc. instead of silver oxide were used as the silver sources, which shows that the IL [Hbet][TFSA] may be superior on Ag recovery from Ag₂O coin batteries.…”
mentioning
confidence: 99%
“…29,35 The influence of water on the electrochemical behavior of Zn(II) and on the morphology of deposited Zn from IL-water mixtures has also been reported. 26,[36][37][38][39][40] MacFarlane et al showed that the favorable electrochemistry of different ionic liquids with different amounts of water and Zn precursors can be due to the formation of different Zn complexes in the IL/water mixtures. 26 In the present study, various concentrations of water have been added to Zn(OAc) 2 /[EMIm]OAc mixtures to investigate the feasibility of Zn electrodeposition at lower concentrations of Zn(OAc) 2 (e.g.…”
mentioning
confidence: 99%